Efektivitas Model Quantum Learning terhadap Minat Siswa pada Pembelajaran Bahasa Arab di Madrasah - Mufidah, Lailatuz Zakiyatul; Rokhmatulloh, Nur (Department of Arabic Education - Faculty of Educational Sciences, 2023)
Quantum Learning model is a learning model that can increase student interest, because it can create a comfortable atmosphere and is not easily boring, and teachers are not fixated on monotonous learning and LKS books, the sample of this study is at MA NU Sunan Giri Prigen, especially class X IIS students totaling 20 students. This type of research uses survey research with quantitative methods, data collection is carried out by observation, interviews, questionnaires or questionnaires and documentation, while the results obtained from taking the data are high categories of student interest in learning Arabic, with an average percentage of 60%, and has a percentage of 71.2% for the strong influence on quantum learning models on student interest. Based on the results of the research above, it can be concluded that the quantum learning model on the interest of class X IIS students at MA NU Sunan Giri Prigen is said to be influential and proven effective.